Genealogia de uma operação historiográfica: as apropriações dos pensamentos de Edward Palmer Thompson e de Michel Foucault pelos historiadores brasileiros na década de 1980 - Ramos, Igor Guedes [UNESP] (2014)
Between 1960 and 1980s were published the major historical research of Edward Palmer Thompson and Michel Foucault. These researches, each in its own way, significantly impacted world historiographical production, setting problems, controversies and transforming the ways to make history. This thesis has studied this impact in the 80s Brazilian historiography, when was inaugurated the systematic appropriation of the thoughts of Thompson and Foucault by Brazilians historians, and also when certain singular theoreticalmethodological experimentations occurred as the simultaneous use of these intellectuals disregarding their epistemological differences. For this venture theses and dissertations defended between 1980 and 1990s in the post graduation programs at USP, UNICAMP, UNESP (Assis), UFPR, UFF e UFRJ, (covering about 65% of the total production of monographs of the period); as well as interviews, journals, books, among others documents relating to the subject. To attend the needs of this study the exposure was structured in two parts: the first part were discussed life experiences, books, theoretical-methodological conceptions, political activities, some of the main interlocutors of Thompson and Foucault and, finally, divergences and similarities between them were observed. In the second part were examined different elements that has constituted the Brazilian historiographical operation in the transition from 70 to 80 and that influenced the appropriation of the thoughts of the English historian and the French philosopher. These elements are related to institutional and ethical-political changes, the theoretical-methodological conceptions and predominant forms of writing, materials means of reception and the different speeches that sought to give direction to the appropriation process. Finally, the ways as the Brazilians historians of the 80s have used elements of the thoughts of Thompson and Foucault in their researches were described ...